Influence of Islamic philosophy on the faith and practices of patients with diabetes mellitus and its musculoskeletal manifestations - Firdaus, Mohd Khairul Zul Hasymi; Hatthakit, Urai; Kongsuwan, Waraporn; Che Hasan, Muhammad Kamil (Universitas Indonesia, 2020)
Transcultural care is an important aspect of patient care. This review paper discusses the influence of Islamic philosophy on the faith and practices of Muslim patients with diabetes mellitus and its musculoskeletal manifestations. Relevant articles were searched from the electronic databases Cumulative Index of Nursing and Allied Health Literature, PubMed, ProQuest, and Science Direct using the keywords “Islamic philosophy, the influence of Islamic Philosophy in Muslim patients, religious practice during sick, fasting months, and sick.” No time limitation was specified for article selection. The database search yielded 170 potential articles. The abstracts of these articles were screened, and 50 full-length manuscripts were obtained, reviewed, and analyzed for their relevance to the subject matter. Discussions rooted in the ontology, epistemology, and methodology of Islamic philosophy were described in detail to provide a sound understanding its influence on Muslim patients. The ontology of Islamic philosophy is based on four important concepts, namely, the Unity of Allah, the Unity of Creation, the Unity of Thought, and the Unity of Man. The epistemological approach can help Muslim patients search for knowledge on the basis of ontology and three principles, namely, Ilm’ Yaqin, Ainul Yaqin, and Haqqal Yaqin. The ontology and epistemology shape the methodology of Muslim patients’ daily life -according to the Islamic concepts of the Five Pillars and Six True Faiths. The issues patients with diabetes mellitus and its musculoskeletal manifestations encounter usually arise when they need to perform obligations during fasting and prayers. Understanding Islamic philosophy in caring for patients with diabetes is important among healthcare professionals to provide appropriate care. Better healthcare services may be provided to Muslim patients if their specific needs of are fulfilled according to their beliefs and culture.